Protection of the child right to privacy in a criminal procedure and media reporting - Stevanović Ivana (Temida, 2008)
Practice demonstrates the importance of raising awareness about the problem of violence against children as well as the necessity of full protection of the right to privacy of minors as participants of criminal proceedings. Journalists must have special knowledge in order to report on criminal justice proceedings dealing with minors. On the other hand, authorized representatives of departments and institutions that participate in criminal justice protection of minors must be trained to present information to the media in a manner that would hinder its random interpretation in public information resources. Furthermore, the author insists on the practical obligation of the state to take systemic measures in suppressing and protecting minors from violations of their right to privacy and the consistent sanctioning of any violation of this right by representatives of the media, as well as by professionals authorized for protection of the right to privacy of minors.